Electronic Energy Transduction from Ru(py)4 - Cadranel, Alejandro; Oviedo, Paola S.; Albores, Pablo; Baraldo, Luis M.; Guldi, Dirk Michael; Hodak, Jose H. (Inorganic Chemistry)
Despite the large body of work on Ru(bpy)2 sensitizer fragments, the same attention has not been devoted to their Ru(py)4 analogues. In this context, we explored the donor-acceptor trans-[Ru(L)4(μ-NC)Cr(CN)52]4-, where L = pyridine, 4-methoxypyridine, 4-dimethylaminopyridine. We report on the synthesis and the crystal structure as well as the electrochemical, spectroscopical, and photophysical properties of these trimetallic complexes, including transient absorption measurements. We observed emission from chromium-centered d-d states upon illuminating into either MLCT or MM′CT absorptions of Ru(L)4 or Ru-Cr, respectively. The underlying energy transfer is as fast as 600 fs with quantum efficiencies ranging from 10% to 100%. These results document that Ru(py)4 sensitizer fragments are as efficient as Ru(bpy)2 in short-range energy transfer scenarios.
CRIS-Team Scopus Importer:2022-04-14